Impact of course length on swimming performance across age groups and swimming strokes - Iglesias García, Javier; Hermosilla-Perona, Francisco; Gonjo, Tomohiro; Juárez Santos-García, Daniel (Frontiers in Sports and Active Living, 2025)
IntroductionSwimmers typically achieve faster times in the same distance events in short course (SC) than in long course (LC) due to the higher number of turns in SC; however, the influence of age and sex on performance differences between SC and LC events remains unclear.MethodsThis study aimed to examine the differences in the top 200 seasonal times between SC and LC in the 50, 100 and 200 m backstroke, breaststroke, butterfly, freestyle and individual medley events (200 and 400 m). Top 200 Spanish seasonal times of four age groups were considered for both sexes between two seasons. A three-way ANOVA with post-hoc analysis was performed to assess the impact of age, sex, and event type on the time differences between SC and LC.ResultsThe results indicated that older swimmers showed greater differences between SC and LC times compared to other age groups in males and females (p < 0.05). In backstroke and breaststroke events, similar patterns were observed with higher differences between SC and LC compared to butterfly and freestyle, especially in 100 m and 200 m events (p < 0.05).DiscussionThese differences should be taken into consideration by coaches and swimmers when establishing differences in performance depending on the pool length.